Brain Stem and Inner Ear Abnormalities in Children with Auditory Neuropathy Spectrum Disorder and Cochlear Nerve Deficiency - Huang, B.Y.; Roche, J.P.; Buchman, C.A.; Castillo, M. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Cranial abnormalities, including CND, are common in children with ANSD. The purpose of this study was to assess whether CND is associated with brain or inner ear abnormalities in a cohort of children with ANSD. MATERIALS AND METHODS: Two neuroradiologists retrospectively reviewed cranial MR imaging examinations in 103 children with ANSD. Brain, cochlear nerve, and temporal bone abnormalities were described and tabulated. Findings were stratified on the basis of the presence and laterality of CND, and differences in the presence of associated inner ear or intracranial abnormalities were assessed by using 2-tailed Fisher exact tests. RESULTS: CND was identified in 33.0% of children and 26.9% of ears with ANSD. Significantly more patients with bilateral CND had intracranial abnormalities than those with unilateral CND (60.0% versus 15.8%; P = .012). Forty percent of patients with bilateral CND, 0% of patients with unilateral CND, and 10.1% of those without CND demonstrated hindbrain malformations. Patients with bilateral CND were more likely to demonstrate hindbrain malformations than patients with normal nerves (P = .01) or unilateral CND (P = .004). Labyrinthine abnormalities were significantly more common in patients with bilateral CND than in those without CND (P ≤ .001). Cochlear anomalies were more common in patients with bilateral versus unilateral CND (P = .01). IAC and cochlear aperture stenosis were more common in those with unilateral and bilateral CND than those without CND (both P < .001). CONCLUSIONS: Cochlear and hindbrain abnormalities are significantly more common among patients with ANSD with bilateral CND compared with those with at least 1 intact cochlear nerve. AanteriorABIauditory brain stem implantationANSDauditory neuropathy spectrum disorderBCNCbony cochlear nerve canal (cochlear aperture)CISSconstructive interference in steady stateCNVIIIvestibulocochlear nerve (eighth cranial nerve)CNDcochlear nerve deficiencyFAflip angleIACinternal auditory canalMCPmiddle cerebellar pedunclePposteriorPVLperiventricular leukomalaciaSCCsemicircular canalSNHLsensorineural hearing lossWMwhite matter